TEACHING READING COMPREHENSION BY EXPERIENCE-TEXT-RELATIONSHIP (ETR) STRATEGY TO THE EIGHT GRADE STUDENTS OF SMP SANDIKA PALEMBANG - Mensi Resolusi (Edukasi, 2015)
The objective of the study is to find out whether or not there is a significant different on students’ reading comprehension who were taught using Experience- Text- Relationship (ETR) Strategy and who were taught using method usually used by teacher to the eighth grade students of SMP SANDIKA Palembang. The population of the study was the Eighth Grade Students of SMP SANDIKA Palembang in the academic year of 2013/2014. The sample of the study was taken from convenience sampling. The writer was selected the class VIII 2 as the control group and VIII 1 as the experimental group. It consisted of 83 students, 40 students for control group and 43 students for experimental group. In this study, the writer used quasi experimental design. The instrument used in collecting the data was written test. The test was administered twice, as the pre-test and post-test for both control and experimental group. The results of the test were analyzed by using t-test. The result showed that teaching reading using ETR had a significant difference on the students’ comprehension. It can be seen from the result of pretest to post-test of each group. The achievement of experimental group was higher than the achievement of control group. Based on the independent t-test analysis from students’ pretest to posttest score in experimental group taught using Experience – Text - Relationship (ETR) strategy, it was found that t-output was lower than p-value or t-obtained was higher than t-table. From the table analysis, p-output was 0.000 and the t-obtained 7.312. The result was consulted to t-table at the significance level 0.05 in two-tailed testing with the degree freedom (1.989). since the p-output was lower than 0.05 level than t-value was higher than critical value of t-table, so the Ho (the null hypotheses) was rejected and the Ha (the alternative hypotheses)  was accepted. It means that there was a significant difference on students’ reading comprehension taught using Experience- Text- Relationship (ETR) strategy of SMP SANDIKA Palembang.